2006
DOI: 10.1097/01.mib.0000231576.11678.57
|View full text |Cite
|
Sign up to set email alerts
|

Frequent detection of cytomegalovirus in the intestine of patients with inflammatory bowel disease

Abstract: Patients with ulcerative colitis had more often detectable CMV genome in their blood as well as in their intestinal tissue samples as compared with controls (P = 0.022 and P < 0.0001, respectively). However, patients with Crohn's disease had more often detectable CMV genome only in their intestinal tissue samples as compared with controls (P = 0.001). Detection of CMV genome in blood or intestinal tissue was significantly associated with short duration of IBD (P = 0.0088 and 0.04, respectively) but not with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 29 publications
3
80
1
17
Order By: Relevance
“…Colonic infection with cytomegalovirus (CMV) has been increasingly implicated in inflammatory bowel disease (IBD) (1)(2)(3). In an immunocompromised host, a primary CMV infection or the reactivation of a latent CMV infection can cause severe disseminated disease, including colitis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Colonic infection with cytomegalovirus (CMV) has been increasingly implicated in inflammatory bowel disease (IBD) (1)(2)(3). In an immunocompromised host, a primary CMV infection or the reactivation of a latent CMV infection can cause severe disseminated disease, including colitis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed CMV positivity in surgical specimens among UC patients who underwent colectomy, and found a strong relationship between CMV colitis and steroid-refractoriness or development of toxic megacolon. Kambhan et al (15) compared the histopathological features of steroid-responsive and steroid-refractory UC patients and showed that CMV colitis was significantly more prevalent in refractory patients, and several studies found high prevalences of CMV colitis among IBD patients with active disease, ranging from 15.8-27.1% (5,19).…”
Section: Resultsmentioning
confidence: 99%
“…CMV infection in the GI tract may develop in all locations, from the mouth to the rectum, and it generally manifests with formation of ulcers on the mucosa, frequently accompanied by hemorrhage (1). In immunocompromised IBD patients, the risk for CMV infection rises, although it does not always lead to clinically active disease (19) or the necessity of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Estudios de cohorte informan una prevalencia de reactivación viral que varía entre 4,6 y 25% [38][39][40][41][42][43][44] .…”
Section: Rol De Citomegalovirus En Crisis Grave De Enfermedad Inflamaunclassified
“…La detección tisular es superior a las técnicas en sangre, ya que permite buscar evidencia de replicación local en biopsias de colon, ya sea mediante tinción con hematoxilina-eosina (sensibilidad 30-50%), inmunohistoquímica (IHQ, sensibilidad 60-90%) o reacción de polimerasa en cadena (RPC, sensibilidad mayor a 90%) 29,31,49 . En las publicaciones más recientes, las técnicas más utilizadas son inmunohistoquímica o RPC en biopsia de mucosa colónica, dada su mayor sensibilidad [38][39][40][41][42][43] .…”
Section: Rol De Citomegalovirus En Crisis Grave De Enfermedad Inflamaunclassified